Students' Mathematical Communication Ability Judging from Self-Confidence and Cognitive Style in Missouri Mathematics Project Learning with Fast Feedback (Unnes Journal of Mathematics Education Research, 2022)
The purpose of this study was to describe the mathematical communication ability of class VIII students of SMP Islam Tunas Harapan in terms of self-confidence and cognitive style. This research is qualitative with data triangulation. The population of this study were students of class VIII SMP Islam Tunas Harapan in the 2022/2023 academic year. Determining research subjects using purposive sampling technique, so that 6 subjects were obtained, namely the categories of high self-confidence reflective, high self-confidence impulsive, moderate self-confidence reflective, moderate self-confidence impulsive, low self-confidence reflective, and low self-confidence impulsive. The results of this study show that students with high self-confidence reflective are able to master all indicators of mathematical communication ability, students with high self-confidence impulsive are only able to master three indicators of mathematical communication ability, students with moderate self-confidence reflective are able to master all indicators of mathematical communication ability, students with moderate self-confidence impulsive are only able to master two indicators of mathematical communication ability, students with low self-confidence reflective are only able to master three indicators of mathematical communication ability, and students with low self-confidence impulsive is only able to master one indicator of mathematical communication ability.